AB0088 Transgenic ZAP-70+ B Cells Mice Show A More Severe Collagen Antibody Induced Arthritis (CAIA) than Wild Type. (15th July 2016) - Biscetti, F.; Angelini, F.; Gobessi, S.; Gremese, E.; Tolusso, B.; Efremov, D.; Ferraccioli, G.
Abstract : Background: Zeta-chain-associated protein kinase 70 (ZAP-70), a tyrosine kinase constitutively expressed in T cells, can be found in B cells and is used as a prognostic marker in identifying different forms of chronic lymphocytic leukemia. We previously provided evidence that a subset of B cells in patients with rheumatoid arthritis (RA) expresses ZAP-70, that marks the memory B cell subsets (IgD+CD27+ and IgD-CD27+), thus suggesting that the ZAP-70+ B cells represent a memory activated subset likely involved in the maintenance of an activated B cell pool [1–3]. Objectives: The aim of the present study was to clarify whether B cells, especially ZAP-70 expressing B cells, represent indeed a risk for a severe expression of arthritis in a transgenic ZAP-70+B murine model. Methods: Male transgenic ZAP-70+B mice, that has already been shown to present an high ZAP-70 expression in the B cell lineage [4], aged 8–12 weeks old were used for experiments. All the animals were injected with a cocktail of 5 monoclonal antibodies recognizing the conserved epitopes on various species of type II collagen. Three days later the mice were injected with LPS from E. coli 0111:B4 to trigger arthritis development. Animals were evaluated every 3 days after the infusion of the antibody cocktail for arthritis incidence and each paw was evaluated and scored individually on a scale of 0–4. An arthritis index (AI) that expressed a cumulative score for all paws was calculated for each animal. Results: We found that the transgenic ZAP-70+B cells mice presented a more severe form of arthritis, compared to wild type age-matched mice (p<0.001) (Figure ). Histological and immunohistochemical analyses confirmed the presence of joint erosions and inflammatory infiltrate at the level of the synovium of ZAP-70+B cells mice. Conclusions: These data suggest that B cells amplify the degree of CAIA, that ZAP-70 is involved in the pathogenesis of arthritis in an RA-like model, and that this tyrosine kinase likely represents a possible target of therapy. References: Tolusso B, et al. Clin Immunol. 2009 Apr;131(1):98–108 Michelutti A, et al. Mol Med. 2011 Sep-Oct;17(9–10):901–9 Gremese E, et al. J Rheumatol. 2012 Dec;39(12):2276–85 Gobessi S, et al. Blood (ASH Annual Meeting Abstracts) 2011 118: Abstract 2830? Disclosure of Interest: None declared